A novel cascaded multilevel converter topology based on three-phase cells - Camargo, Renner Sartório (2021)
Due to the structural characteristics of modern electrical grids, the use of equipment based on power electronics to guarantee its perfect functioning has grown sharply, encouraging the study and development of equipment based on these technologies like converters with multiple voltage levels, known in the literature as multilevel converters. Multilevel converters based on H bridge cells, known in the literature as CHB (Cascaded H bridge Converter) are the most outstanding among this converters category, however, the natural switching of the multilevel CHB converter in specific configurations, such as a back-to-back connection (CHB-B2B), presents several short-circuit states, making its performance unfeasible or limiting. This issue may require additional stages of isolation, increasing its implementation cost and reducing its competitiveness. Under these circumstances, this work proposes a new multilevel converter topology based on H bridge cells, without isolation stages, with three-phase characteristics and superiority in some metrics compared to a CHB of the same specifications. It also has a lower number of components, lower construction cost, and similar performance. This newly proposed topology, named SDC-CHB (Cascaded H Bridge Converter with Single DC-link), also features several short-circuit states as well as CHB. However, the use of graph theory and model-based predictive control (MPC) enables the inhibition of the short-circuit stages inherent to the SDC-CHB topology. This work is also dedicated to the mathematic study and the mapping of the SDC-CHB short circuit states in a STATCOM as a power electronic application, and comparing its performance with this device using a CHB converter with similar characteristics. This topology was subjected to simulations in Simulink Matlab software for data analysis and later implemented on a hardware-in-the-loop (HIL) real-time platform from the manufacturer OPAL-RT, model 5700, to prove its applicability and to validate the proposal. To analyze the efficiency of the converter, measurements of losses by conductivity and switching were carried out using the PLECS® Plexim software, where the energy consumption of the converter in different modes of operation can be observed.